if we add one to the numerator and subtract I from denominator fraction reduces to one it becomes
![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B2%7D+)
if we add l to the denominator what is fraction
Answers
Answered by
4
Here is ur answer hope it helps....
Attachments:
![](https://hi-static.z-dn.net/files/d05/17005bb5f42b5522dec450e1b58d4e90.jpg)
Answered by
6
Let the Numerator of Fraction =x
Denominator of fraction. =y
![required \: fraction \: is = \frac{x}{y} required \: fraction \: is = \frac{x}{y}](https://tex.z-dn.net/?f=required+%5C%3A+fraction+%5C%3A+is+%3D++%5Cfrac%7Bx%7D%7By%7D+)
According to lst condition
![\: \: \: \: \: \: = \frac{x + 1}{y - 1} = 1 \\ \: \: \: \: \: \: = x + 1 = y - y \\ \: \: \: \: \: \: = x - y + 2 = 0 \: \: \: \: \: (1) \\ \: \: \: \: \: \: = \frac{x + 1}{y - 1} = 1 \\ \: \: \: \: \: \: = x + 1 = y - y \\ \: \: \: \: \: \: = x - y + 2 = 0 \: \: \: \: \: (1) \\](https://tex.z-dn.net/?f=++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%3D+%5Cfrac%7Bx+%2B+1%7D%7By+-+1%7D++%3D+1+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%3D+x++%2B+1+%3D+y+-+y+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%3D+x+-+y+%2B+2+%3D+0+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+%281%29+%5C%5C+)
According to the second condition
![\: \: \: \: \: \: \: \: \: \: \frac{x}{y + 1} = \frac{1}{2} \\ \: \: \: \: \: \: \: \: \: 2x \: \: \: \: \: \: \: = y + 1\\ 2x - y - 1 =0 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (2) \: \: \: \: \: \: \: \: \: \: \frac{x}{y + 1} = \frac{1}{2} \\ \: \: \: \: \: \: \: \: \: 2x \: \: \: \: \: \: \: = y + 1\\ 2x - y - 1 =0 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: (2)](https://tex.z-dn.net/?f=++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5Cfrac%7Bx%7D%7By+%2B+1%7D++%3D+++%5Cfrac%7B1%7D%7B2%7D+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+++%5C%3A++%5C%3A++%5C%3A++2x+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+++%3D++y+%2B+1%5C%5C+2x+-+y+-+1+%3D0+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+%282%29)
Now (2)-(1) gives
![2x - y - 1 = 0 \\ x - y + 2 \: \: =0 \\ - \: \: \: + \: \: \: \: \: \: - \\ \: \: \: \: \: \: \: \: \: \: \: x - 3 = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = 3 2x - y - 1 = 0 \\ x - y + 2 \: \: =0 \\ - \: \: \: + \: \: \: \: \: \: - \\ \: \: \: \: \: \: \: \: \: \: \: x - 3 = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = 3](https://tex.z-dn.net/?f=2x+-+y+-+1+%3D+0+%5C%5C+x+-+y+%2B+2+%5C%3A++%5C%3A++++%3D0+%5C%5C++-++%5C%3A++%5C%3A++%5C%3A++%2B++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++-++%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+x+-+3+%3D+0+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+x+%3D+3)
substiutue the value of x in (2) we get
![2 \times 3 - y - 1 = 0 \\ \: \: \: \: \: \: \: \: 6 - y - 1 = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 5 - y = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = 5 \\ hence \: required \: fraction \: is \: \frac{3}{5} 2 \times 3 - y - 1 = 0 \\ \: \: \: \: \: \: \: \: 6 - y - 1 = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: 5 - y = 0 \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: y = 5 \\ hence \: required \: fraction \: is \: \frac{3}{5}](https://tex.z-dn.net/?f=2+%5Ctimes+3+-+y+-+1+%3D+0+%5C%5C+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+6+-+y++-+1+%3D+0+%5C%5C+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++5+-+y+%3D+0+%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+y+%3D+5+%5C%5C+hence+%5C%3A+required+%5C%3A+fraction+%5C%3A+is+%5C%3A++%5Cfrac%7B3%7D%7B5%7D+)
Denominator of fraction. =y
According to lst condition
According to the second condition
Now (2)-(1) gives
substiutue the value of x in (2) we get
Similar questions